2009
DOI: 10.1590/s0004-282x2009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of headaches in the premenstrual tension syndrome

Abstract: -Objective: Characterization of headaches in premenstrual syndrome (PMS). Although headache is one of the symptoms for PMS, no details on this headache are given by the American College of Obstetrics and Gynecology (ACOG) criteria. Method: A group of 45 fertile age women presenting PMS were invited to complete a registration diary for headache and PMS symptoms for three consecutive months. The diary included details of each headache attack, allowing for classification according to the International Headache So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…PMS associated with menstrual migraine has been evaluated and increased symptoms of PMS associated with menstrual migraine were observed [18][19][20][21][22][23][24][25]. It is therefore suggested that all women with PMS be examined for the presence of menstrual migraine using IHS criteria (International headache society) as medical and social consequences of menstrual headache affect not only the women but also their family [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMS associated with menstrual migraine has been evaluated and increased symptoms of PMS associated with menstrual migraine were observed [18][19][20][21][22][23][24][25]. It is therefore suggested that all women with PMS be examined for the presence of menstrual migraine using IHS criteria (International headache society) as medical and social consequences of menstrual headache affect not only the women but also their family [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Vetvik, from a total of 237 students with PMS, 7.6% had menstrual migraine [20]. In the study of Fragoso, the most common type of headache was migraine without aura with a prevalence of 60% among 45 women with PMS [22]. In the study of McGregor, 7.2% of 55 women with PMS had migraine without aura [24].…”
Section: Discussionmentioning
confidence: 99%
“…In women with PMS, severe headache outbreaks during the luteal phase and an increase in headache resistance to painkillers and anti-inflammatory drugs lead to increase in depression, irritability, anxiety, anger, and food intolerance during the luteal phase [3739]. Cady et al [40] reported that ginger administration caused a significant deceleration in severity of headache in patients with migraine [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fragoso et al [8] tried to characterize the type of headache occurring in the PMS and to evaluate its exact prevalence. Their diary-based study showed that migraine without aura was the most common type of headache, being present in 60 % of PMS sufferers, followed by TTH (30 %).…”
Section: Association Between Menstrual Migraine and Premenstrual Syndmentioning
confidence: 99%
“…In women suffering from both MM and PMS, headache attacks tend to be more severe, longer and less responsive to treatment and PMS symptoms are also more disabling when compared with women suffering from TTH during the PMS [8].…”
Section: Treatment Strategies For MM In the Context Of Pmsmentioning
confidence: 99%